2023
DOI: 10.22317/imj.v7i2.1219
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of Endolimax species recognized in human and animals, a review on a neglected intestinal parasitic amoeba

Abstract: Objectives: Endolimax is a protozoan genus belongs to Amoebida order. The member of this genus occurrence in a vast range of vertebrate and invertebrate, but the species of this genus are not well studied. This review aimed to provide an updated list and some summarized information on Endolimax species, which were identified in human and animals up to the 2023. Methods: The present study was carried out to evaluate the Endolimax species with a broad review of the literature, books and electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The intestinal colonization with Endolimax occurs after ingestion of mature cysts via the oral-fecal route. The trophozoite originates from the cyst and multiplies by binary fission in the host [25] where it feeds exclusively on bacteria [286]. The cysts are excreted in feces and can survive for two weeks at room temperature and two months at lower temperatures [25].…”
Section: Endolimax Nanamentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal colonization with Endolimax occurs after ingestion of mature cysts via the oral-fecal route. The trophozoite originates from the cyst and multiplies by binary fission in the host [25] where it feeds exclusively on bacteria [286]. The cysts are excreted in feces and can survive for two weeks at room temperature and two months at lower temperatures [25].…”
Section: Endolimax Nanamentioning
confidence: 99%
“…nana is considered a commensal in the colon and appendix but rare cases of abdominal pain, diarrhea, polyarthritis, and urticaria were found to be associated with this protozoan. A systematic review of E. nana prevalence showed that most data were obtained from general studies on intestinal parasites and very few case reports are available [25]. A recent case of chronic urticaria and prolonged occasional abdominal pain and diarrhea with weight loss after a journey to Vietnam involved a 34-year-old Italian woman.…”
Section: Endolimax Nanamentioning
confidence: 99%